Activity Test of Daun Jati Belanda (Guazuma ulmifolia Lamk.) on Lymphocyte Proliferation and Immunoglobulin G Expressionas an Immunostimulatory Agent - Yanna Rotua Sihombing; Fitri Siska (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Infections that attack the immune system have become a major global health issue, including in Indonesia. In 2019, the emergence of Coronavirus created an urgent need for immediate therapy, followed by increased attention to other diseases such as tuberculosis (TB), PCP pneumonia (Pneumocystis jirovecii), candidiasis, and toxoplasmosis. If left untreated, infections can damage tissues and organs. Although immune-boosting drugs are available in healthcare settings, their side effects and potential drug interactions highlight the need for complementary therapies derived from natural ingredients. Indonesia’s biodiversity offers great potential for the development of natural immunostimulants. One such plant is Jati Belanda (Guazuma ulmifolia Lamk.), which is widely found in Deli Serdang, North Sumatra. Empirically, its leaves have been used to treat diarrhea, cough, abdominal pain, and as a tonic and astringent. Research has shown that Guazuma ulmifolia contains alkaloids, tannins, and flavonoids with antihyperlipidemic, antiviral, and anti-inflammatory properties, as well as potential immune-enhancing effects.Objective: This study aimed to analyze the immunostimulatory activity of Guazuma ulmifolia leaf extract on lymphocyte proliferation and IgG expression using male rats. Methods: The experimental method was applied, including a lymphocyte proliferation assay using the MTT method and serum IgG measurement using the ELISA technique. Results: The results showed that the extract significantly increased lymphocyte proliferation and IgG levels. The EC50 value of the extract (4.720 µg/mL) was comparable to that of Imboost (4.282 µg/mL), indicating similar effectiveness. Increased absorbance at various extract concentrations reflected enhanced cell proliferation. A dose of 400 mg/kg body weight effectively elevated IgG levels, strengthening the humoral immune response. The presence of flavonoids, tannins, and saponins is thought to play a role by activating B cells, promoting plasma cell differentiation, and modulating the NF-κB signaling pathway. Conclusion: Therefore, Guazuma ulmifolia leaf extract has potential as a natural immunostimulant that supports the body’s defense against pathogens.